2018
DOI: 10.30597/mkmi.v14i3.4604
|View full text |Cite
|
Sign up to set email alerts
|

Level Aktivitas Fisik dan Kualitas Hidup Warga Lanjut Usia

Abstract: Penelitian terdahulu menunjukkan bahwa partisipasi aktif dalam kegiatan olahraga merupakan faktor utama yang berhubungan dengan kualitas hidup peserta posyandu lanjut usia (lansia). Oleh karena itu, penelitian ini dilakukan untuk mengetahui hubungan level aktivitas fisik dan kualitas hidup lansia di Kecamatan Bambanglipuro, Bantul. Suatu studi cross-sectional dilaksanakan selama Juni-September 2017. Sampel adalah 123 subjek lansia di Bambanglipuro yang terpilih melalui teknik consecutive sampling. Level aktivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
12

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 23 publications
1
13
0
12
Order By: Relevance
“…Elderly people who stay at home for active participation in sports activities are the main factors related to the quality of life of elderly Posyandu participants (elderly). According to Dewi researchers, physical activity or sports activities are closely related to the quality of life of the elderly (Dewi, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Elderly people who stay at home for active participation in sports activities are the main factors related to the quality of life of elderly Posyandu participants (elderly). According to Dewi researchers, physical activity or sports activities are closely related to the quality of life of the elderly (Dewi, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Life expectancy is also closely related to the quality of mental and physical health, especially in the elderly. A research by Dewi (2018) in Bantul Regency (Yogyakarta) showed that the gender factor was also not significantly related to the quality of mental and physical health of the elderly population.…”
Section: Discussionmentioning
confidence: 97%
“…Based on (Indonesian Ministry of Health, 2019) physical activity is useful for improving psychological well-being, self-confidence, controlling stress, anxiety, and depression for the elderly. Dewi's (2018) research shows that subjects with a high level of activity are associated with good health conditions and mental health quality. The elderly can be said to have a good quality of life if they show a condition that states the level of satisfaction in the mental, physical, social, comfort, and happiness aspects of their life.…”
Section: Discussionmentioning
confidence: 99%